South African Englishes: A contemporary bibliography. Issue 1 (30th March 2020) - Botha, Werner; van Rooy, Bertus; Coetzee‐van Rooy, Susan
Abstract: The bibliography presented here is a list of contemporary research publications that provide the details of books, research articles, as well as other research outputs that were published between 1994 and 2020. The main aim of this bibliography is to provide scholars interested in researching South African Englishes with sources of major works published internationally as well as in core journals from South Africa. Despite the problems concerning representativeness of research bibliographies, we hope that this list of references will complement existing sources in the field. We also hope that this bibliography will serve as a useful guide for those researchers and graduate students interested in contemporary issues in the study of South African Englishes.